Method for testing impermeability of paper and application thereof

By using non-toxic testing solutions and simple testing steps, the complex operational and safety risks of anti-permeability detection in the prior art are solved, and high accuracy and safety detection results are achieved.

CN119438035APending Publication Date: 2025-02-14NANTONG CIGARETTE FILTER
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411706056.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing anti-permeability detection methods for cigarette paper and molded paper for cigarettes have problems such as complex operation, inaccurate control of test conditions, high risk, and incorrect proportion of mixed reagents. The toluene used is a toxic substance, which poses a safety risk.

Method used

Provide a paper anti-permeability test method, using a non-toxic test solution, including a mixture of mineral oil and n-alkanes, to determine the anti-permeability level by dropping the test solution and observing whether it penetrates. It is simple to operate, high safety, and can Effectively control the test conditions.

Benefits of technology

It improves the accuracy and reproducibility of the test results, avoids the use of toxic reagents such as toluene, which are simple to operate, widely applicable and highly safe.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005154539640000011
    Figure BDA0005154539640000011
  • Figure BDA0005154539640000021
    Figure BDA0005154539640000021
  • Figure BDA0005154539640000081
    Figure BDA0005154539640000081
Patent Text Reader

Abstract

The invention provides a method for testing the impermeability of paper and application thereof, and the method comprises the following steps: (1) placing a test surface of a test sample upwards, and then dropwise adding a test solution above the test surface; (2) removing the test solution, and observing the dripping area of the test solution; (3) if the first test reaches a test end point, repeating the steps (1) and (2) in different test areas by adopting test solutions with lower serial numbers in sequence for testing until the test end point does not appear any more; if the first test does not reach the test end point, the test solutions with higher numbers are adopted in sequence to repeat the step (1) and the step (2) in different test areas for testing until the test end point appears; (4) determining the anti-permeation grade of the test sample according to a test result; the test method provided by the invention is simple to operate, the used reagent is non-toxic and high in safety, the test condition can be effectively controlled, the accuracy and reproducibility of the test result are improved, and the applicability is wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of tobacco material detection, and specifically relates to a method for testing the anti-permeability performance of paper and an application thereof, and in particular to a method for testing the anti-permeability performance of paper with high accuracy and an application thereof. Background Art

[0002] At present, the main method for testing the anti-permeability performance of cigarette paper and plug-in paper is the Kit method. The test steps of the Kit method are:

[0003] 1. Arrange the paper sample into a flat shape. The test surface cannot be touched by hands.

[0004] 2. With the test surface facing upward, drop a drop of test liquid with a known Kit number at a height of 25 mm.

[0005] 3. After 15 seconds, use toilet paper to remove the remaining test liquid.

[0006] 4. Immediately observe whether the back of the oil droplet has been penetrated and changed color.

[0007] 5. Repeat the test until the paper surface of the kit number test liquid is no longer penetrated and changes color.

[0008] 6. The oil resistance of the paper sample is the value of the Kit number.

[0009] The components of the standard test solution of the Kit method are as follows:

[0010]

[0011]

[0012] When using the Kit method to measure the penetration resistance level, there are problems such as complex operation, imprecise control of test conditions, and high risk. At the same time, the test solution used in the Kit method needs to be mixed with castor oil, toluene, and heptane in different proportions. There are risks such as wrong mixing ratio and uneven mixing during the mixing process. At the same time, toluene is a toxic substance, which poses a safety risk.

[0013] CN111474101A discloses a paper penetration rate measuring device and method, the measuring device includes: a conductive plate; an insulating cylinder, the bottom end of which is open, and is provided with a test port and a liquid injection port. When the insulating cylinder is placed on the paper to be tested, the bottom end opening is closed by the paper to be tested; a power supply, one pole of which is connected to one end of a first conductor, and the other end of the first conductor is connected to the conductive plate; the other pole is connected to one end of a second conductor, and the other end of the second conductor passes through the test port, suitable for contacting the paper to be tested or the liquid injected above the paper to be tested in the space surrounded by the insulating cylinder and the paper to be tested; a current sensor, which detects the current in the first conductor or the second conductor. The paper penetration rate measuring device and method replaces the method of indirectly reflecting the liquid penetration speed by measuring the liquid penetration amount, and directly measures the paper liquid penetration rate, which more accurately reflects the paper liquid penetration speed; the measuring device automatically measures the timing, is easy to operate, and has high accuracy of the measuring result. However, it requires the use of a unique device and is complicated to operate.

[0014] Therefore, how to provide a method for testing the anti-permeability performance of paper that is simple to operate, has effectively controlled test conditions, and is highly safe has become an urgent problem to be solved. Summary of the invention

[0015] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for testing the anti-permeability performance of paper and its application, in particular to provide a method for testing the anti-permeability performance of paper with high accuracy and its application. The testing method provided by the present invention is simple to operate, the reagents used are non-toxic, the safety is high, the testing conditions can be effectively controlled, the accuracy and reproducibility of the test results are improved, and the applicability is wide.

[0016] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0017] In one aspect, the present invention provides a method for testing the anti-permeability performance of paper, the testing method comprising the following steps:

[0018] (1) Place the test sample with the test surface facing upward, and then drip the test solution onto the test surface;

[0019] The numbers and compositions of the test solutions are as follows:

[0020] Test solution No. 1, composed of mineral oil;

[0021] Test solution No. 2, composed of a mixture of mineral oil and n-hexadecane;

[0022] Test solution No. 3, composed of n-hexadecane;

[0023] Test solution No. 4, composed of n-tetradecane;

[0024] Test solution No. 5, composed of n-dodecane;

[0025] Test solution No. 6, composed of n-decane;

[0026] Test solution No. 7, composed of n-octadecane;

[0027] Test solution No. 8, composed of n-heptane;

[0028] Test solution No. 9, composed of n-hexane;

[0029] (2) Remove the test solution and observe the area where the test solution is dripped. If the back of the area where the test solution is dripped changes color due to penetration, the test endpoint is reached;

[0030] (3) If the test endpoint is reached in the first test, then repeat steps (1) and (2) in different test areas with test solutions with lower numbers until the test endpoint no longer appears; if the test endpoint is not reached in the first test, then repeat steps (1) and (2) in different test areas with test solutions with higher numbers until the test endpoint appears;

[0031] (4) Based on the test results of step (3), the maximum number of the test solutions that do not reach the test endpoint is used as the anti-permeation grade of the test sample.

[0032] The test solutions of the above-mentioned specific components do not need to be mixed when used except for solution 2#, thus avoiding the risks of incorrect mixing ratios, uneven mixing, etc. in the large-scale mixing process of the existing Kit method, and can effectively control the test conditions, effectively improve the accuracy and reproducibility of the test results, and at the same time avoid the use of toxic reagents such as toluene, with high safety.

[0033] The above test method is simple to operate, the reagents used are non-toxic, and the safety is high. The test conditions can be effectively controlled, the accuracy and reproducibility of the test results are improved, and the applicability is wide.

[0034] Preferably, in the environment of step (1), the temperature is 22-24°C and the relative humidity is 48-52%, wherein the temperature may be 22°C, 22.5°C, 23°C, 23.5°C or 24°C, etc., and the relative humidity may be 48%, 49%, 50%, 51% or 52%, etc., but are not limited to the values ​​listed above, and other values ​​not listed within the above numerical range are equally applicable.

[0035] Preferably, the position of adding the test solution in step (1) is 8-12 mm above the test surface, such as 8 mm, 9 mm, 10 mm, 11 mm or 12 mm, etc., but is not limited to the above-listed values. Other values ​​not listed within the above-listed range are also applicable.

[0036] Preferably, the density of the mineral oil at 20°C is 0.842-0.858 g / cm 3 , the kinematic viscosity at 100°C is 3.0-7.0mm 2 / s.

[0037] Preferably, in the test solution No. 2, the volume ratio of mineral oil to n-hexadecane is (60-70):(40-30), wherein the number of parts of mineral oil can be 60, 61, 62, 63, 64, 65, 66, 67, 68, 69 or 70, and the number of parts of n-hexadecane can be 40, 39, 38, 37, 36, 35, 34, 33, 32, 31 or 30, but are not limited to the values ​​listed above, and other values ​​not listed within the above numerical range are equally applicable.

[0038] Preferably, the anti-permeability grade is divided into 10 grades from 0 to 9; when the test solution No. 1 is used for testing and the test endpoint is reached, the anti-permeability grade of the test sample is level 0; when the test solution No. 9 is used for testing and the test endpoint is not reached, the anti-permeability grade of the test sample is level 9.

[0039] Preferably, the removal of the test solution in step (2) is performed 13-17 seconds after the addition of the test solution, for example 13 seconds, 14 seconds, 15 seconds, 16 seconds or 17 seconds, but is not limited to the above-listed values. Other values ​​not listed within the above-listed range are also applicable.

[0040] Preferably, the interval between the different test areas in step (3) is at least 10 mm.

[0041] Preferably, in the testing method, at least 5 test samples of the same specification are tested, and the minimum value of the anti-penetration grade among them is taken as the anti-penetration grade of the sample of the specification to be tested.

[0042] On the other hand, the present invention also provides the application of the above-mentioned testing method in the performance testing of cigarette paper.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] The invention provides a method for testing the anti-permeability performance of paper, which is simple to operate, uses non-toxic reagents, has high safety, can effectively control test conditions, improves the accuracy and reproducibility of test results, and has wide applicability. DETAILED DESCRIPTION

[0045] In order to further explain the technical means and effects adopted by the present invention, the technical solution of the present invention is further described below in conjunction with the preferred embodiments of the present invention, but the present invention is not limited to the scope of the embodiments.

[0046] In the following example, the mineral oil was purchased from Indonesia's Sinar Mas Group and the model number is paraffin oil.

[0047] Example 1

[0048] This embodiment provides a method for measuring the anti-permeability performance of cigarette paper and plug-in paper for cigarettes, and the specific steps are as follows:

[0049] Test sample forming paper: 19mm×30g / m 2 5 pieces of oil-proof forming paper samples, kit method anti-penetration grade is 5.

[0050] Environment: Temperature is 23.2℃, relative humidity is 50.1%.

[0051] The number and composition of each test solution are as follows:

[0052] Anti-penetration grade Test solution number Test solution composition 0 Failed the mineral oil test —— 1 1 Mineral oil 2 2 Mineral oil: n-hexadecane (65:35) 3 3 n-Hexadecane 4 4 n-Tetradecane 5 5 n-Dodecane 6 6 n-decane 7 7 n-Octane 8 8 n-Heptane 9 9 Hexadecane

[0053] Test steps:

[0054] 1. Place each specimen on a clean, flat test bench with the test surface facing upward.

[0055] 2. Take a sample and a test solution of n-dodecane, and put the test solution in a test bottle. At a height of about 10 mm from the test surface of the sample, drop a drop of the test solution onto the surface of the sample and start the stopwatch.

[0056] 3. After 15 seconds, quickly wipe off the excess test solution with absorbent paper. At the same time, immediately check the area where the test solution dripped. The back of the area where the test solution dripped did not change color due to penetration.

[0057] 4. Take n-decane as the test solution and put it in the test bottle. At a height of about 10 mm from the test surface of the sample, drop a drop of the test solution onto the surface of the sample (10 mm away from the test site in step 2) and start the stopwatch.

[0058] 5. After 15 seconds, quickly wipe off the excess test solution with absorbent paper. At the same time, immediately check the area where the test solution dripped. The back of the area where the test solution dripped changed color due to penetration.

[0059] 6. Determine through steps 1-5 that the anti-penetration level of this sample is level 5.

[0060] 7. Repeat the above steps for the remaining 4 samples, and the anti-penetration level is all 5.

[0061] 8. Take the minimum value of the anti-penetration level of the 5 samples as the test result and determine that the anti-penetration level of this sample is level 5.

[0062] Example 2

[0063] This embodiment provides a method for determining the anti-permeability performance of cigarette paper and plug-in paper. The specific steps are consistent with those of Embodiment 1 except for the following environmental conditions.

[0064] Environment: Temperature is 28°C, relative humidity is 50.1%.

[0065] Example 3

[0066] This embodiment provides a method for determining the anti-permeability performance of cigarette paper and plug-in paper. The specific steps are consistent with those of Embodiment 1 except for the following environmental conditions.

[0067] Environment: Temperature is 17°C, relative humidity is 50.1%.

[0068] Example 4

[0069] This embodiment provides a method for determining the anti-permeability performance of cigarette paper and plug-in paper. In the specific steps, except that the plug-in paper of the test sample is 25g / m 2 Except for 5 pieces of high-transparency packaging paper samples (kit method anti-permeability grade is 2), the rest are the same as Example 1.

[0070] Example 5

[0071] This embodiment provides a method for determining the anti-permeability performance of cigarette paper and plugging paper. The specific steps are consistent with those of Example 1 except that the volume ratio of mineral oil to n-hexadecane in the No. 2 test solution is 55:45.

[0072] Example 6

[0073] This embodiment provides a method for determining the anti-permeability performance of cigarette paper and plugging paper. The specific steps are consistent with those of Example 1 except that the volume ratio of mineral oil to n-hexadecane in the No. 2 test solution is 75:25.

[0074] Comparative Example 1

[0075] This comparative example provides a method for determining the anti-permeability performance of cigarette paper and plug-in paper for cigarettes. The specific steps are consistent with those of Example 1 except that the numbers and compositions of the test solutions are as follows.

[0076] Anti-penetration grade Test solution number Test solution composition 0 Failed the mineral oil test —— 1 1 Mineral oil 2 2 n-Hexadecane 3 3 n-Pentadecane 4 4 n-Tetradecane 5 5 n-Tridecane 6 6 n-Dodecane 7 7 n-Undecane 8 8 n-decane 9 9 n-Neptane

[0077] Comparative Example 2

[0078] This comparative example provides a method for determining the anti-permeability performance of cigarette paper and plug-in paper for cigarettes. The specific steps are consistent with those of Example 1 except that the numbers and compositions of the test solutions are as follows.

[0079]

[0080]

[0081] Effect test:

[0082] (1) The test results of Examples 1-6 and Comparative Examples 1-2 were statistically analyzed, and the results were as follows:

[0083]

[0084] By comparing Example 1 and Comparative Examples 1-2, it is found that the test results of the five samples in Example 1 are consistent with the results of the KIT method, all of which are level 5. The levels of the five samples in Comparative Example 1 are all level 6, which is inconsistent with the KIT method. The levels of the five samples in Comparative Example 2 are level 5 or level 6, and the final level is confirmed to be level 5. It can be confirmed that different solvents will affect the confirmation of the anti-permeation level.

[0085] By comparing Examples 1-3, it is found that different environments may lead to inconsistent final test results.

[0086] Comparative Examples 4-6 show that the different volume ratios of mineral oil and n-hexadecane in test solution No. 2 can lead to inconsistent test results.

[0087] (2) The plugging papers with different anti-permeability levels under the kit method were respectively taken and tested under the conditions of Example 1. The test results are as follows:

[0088] Kit method penetration resistance grade Piece of paper sample Test Results 1 <![CDATA[25g / m 2 High transparency wrapping paper (26000CU)]]> 1 2 <![CDATA[25g / m 2 High transparency wrapping paper (6000CU)]]> 2 3 <![CDATA[32g / m 2 Ordinary wrapping paper]]> 3 4 <![CDATA[60g / m 2 Ordinary wrapping paper]]> 4 5 <![CDATA[30g / m 2 Oil-proof wrapping paper]]> 5 6 <![CDATA[35g / m 2 Oil-proof wrapping paper]]> 6 7 <![CDATA[40g / m 2 Oil-proof wrapping paper]]> 7 8 <![CDATA[60g / m 2 Oil-proof wrapping paper]]> 8 9 <![CDATA[78g / m 2 Oil-proof wrapping paper]]> 9

[0089] Through testing, it was found that the test results of the samples were consistent with the kit method.

[0090] (3) Application example: for 30g / m 2 Oil-proof wrapping paper incoming inspection

[0091] Cut 10 specimens from the sample, with a length of at least 150 mm, and mark the test surface. Among them, 5 specimens are used for testing and the other 5 specimens are reserved.

[0092] Environment: Temperature is 23.2℃, relative humidity is 50.1%.

[0093] Prepare the test solutions with the following numbers and compositions:

[0094]

[0095]

[0096] Test steps:

[0097] 1. Place each specimen on a clean, flat test bench with the test surface facing upward.

[0098] 2. Take a sample and a test solution of n-dodecane, and put the test solution in a test bottle. At a height of about 10 mm from the test surface of the sample, drop a drop of the test solution onto the surface of the sample and start the stopwatch.

[0099] 3. After 15 seconds, quickly wipe off the excess test solution with absorbent paper. At the same time, immediately check the area where the test solution dripped. The back of the area where the test solution dripped did not change color due to penetration.

[0100] 4. Take n-decane as the test solution and put it in the test bottle. At a height of about 10 mm from the test surface of the sample, drop a drop of the test solution onto the surface of the sample (10 mm away from the test site in step 2) and start the stopwatch.

[0101] 5. After 15 seconds, quickly wipe off the excess test solution with absorbent paper. At the same time, immediately check the area where the test solution dripped. The back of the area where the test solution dripped changed color due to penetration.

[0102] 6. Determine through steps 1-5 that the anti-penetration level of this sample is level 5.

[0103] 7. Repeat the above steps for the remaining 4 samples, and the anti-penetration level is all 5.

[0104] 8. Take the minimum value of the anti-penetration level of the 5 samples as the test result and determine that the anti-penetration level of this sample is level 5.

[0105] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the test method and application of the anti-permeability performance of paper of the present invention, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0106] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0107] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

Claims

1. A method for testing the anti-permeability performance of paper, characterized in that: The test method comprises the following steps: (1) Place the test sample with the test surface facing upward, and then drip the test solution onto the test surface; The numbers and compositions of the test solutions are as follows: Test solution No. 1, composed of mineral oil; Test solution No. 2, composed of a mixture of mineral oil and n-hexadecane; Test solution No. 3, composed of n-hexadecane; Test solution No. 4, composed of n-tetradecane; Test solution No. 5, composed of n-dodecane; Test solution No. 6, composed of n-decane; Test solution No. 7, composed of n-octadecane; Test solution No. 8, composed of n-heptane; Test solution No. 9, composed of n-hexane; (2) Remove the test solution and observe the area where the test solution is dripped. If the back of the area where the test solution is dripped changes color due to penetration, the test endpoint is reached; (3) If the test endpoint is reached in the first test, then repeat steps (1) and (2) in different test areas with test solutions with lower numbers until the test endpoint no longer appears; if the test endpoint is not reached in the first test, then repeat steps (1) and (2) in different test areas with test solutions with higher numbers until the test endpoint appears; (4) Based on the test results of step (3), the maximum number of the test solutions that do not reach the test endpoint is used as the anti-permeation grade of the test sample.

2. The testing method according to claim 1, characterized in that: The environment in step (1) has a temperature of 22-24° C. and a relative humidity of 48-52%.

3. The testing method according to claim 1 or 2, characterized in that: The position for dripping the test solution in step (1) is 8-12 mm above the test surface.

4. The testing method according to any one of claims 1 to 3, characterized in that: The density of the mineral oil at 20°C is 0.842-0.858 g / cm 3 , the kinematic viscosity at 100°C is 3.0-7.0mm 2 / s.

5. The testing method according to any one of claims 1 to 4, characterized in that: In the No. 2 test solution, the volume ratio of mineral oil to n-hexadecane is (60-70):(40-30).

6. The testing method according to any one of claims 1 to 5, characterized in that: The anti-penetration grade is divided into 10 grades from 0 to 9; when the test solution No. 1 is used for testing and the test endpoint is reached, the anti-penetration grade of the test sample is 0; when the test solution No. 9 is used for testing and the test endpoint is not reached, the anti-penetration grade of the test sample is 9.

7. The testing method according to any one of claims 1 to 6, characterized in that: The removal of the test solution in step (2) is performed 13-17 seconds after the dropwise addition of the test solution.

8. The testing method according to any one of claims 1 to 7, characterized in that: The interval between the different test areas in step (3) is at least 10 mm.

9. The testing method according to any one of claims 1 to 8, characterized in that: In the test method, at least 5 test samples are tested for the same specification sample to be tested, and the minimum value of the anti-penetration grade among them is taken as the anti-penetration grade of the specification sample to be tested.

10. Application of the test method according to any one of claims 1 to 9 in cigarette paper performance testing.

Citation Information

Patent Citations

  • Paper penetration rate measuring device and method

    CN111474101A